1994
DOI: 10.1128/mcb.14.2.1278
|View full text |Cite
|
Sign up to set email alerts
|

Homologous, homeologous, and illegitimate repair of double-strand breaks during transformation of a wild-type strain and a rad52 mutant strain of Saccharomyces cerevisiae.

Abstract: Different modes of in vivo repair of double-strand breaks (DSBs) have been described for various organisms: the recombinational DSB repair (DSBR) mode, the single-strand annealing (SSA) mode, and end-to-end joining. To investigate these modes of DSB repair in Saccharomyces cerevisiae, we have examined the fate of in vitro linearized replicative plasmids during transformation with respect to several parameters. We found that (i) the efficiencies of both intramolecular and intermolecular linear plasmid DSB repai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
52
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 70 publications
1
52
0
Order By: Relevance
“…Recombination events promoted by very small stretches of homology have been described for experimental systems 23 and for mutations leading to human disease. 24,25 The sequence CTGGT occurs once in intron 3 and twice in intron 7.…”
Section: Discussionmentioning
confidence: 99%
“…Recombination events promoted by very small stretches of homology have been described for experimental systems 23 and for mutations leading to human disease. 24,25 The sequence CTGGT occurs once in intron 3 and twice in intron 7.…”
Section: Discussionmentioning
confidence: 99%
“…In Saccharomyces cerevisiae, efficient DNA repair by SSA requires a minimum of 60 to 90 bp of perfect homology in the regions flanking the DSB (57). A similar intermediate might occur in nonhomologous end joining (NHEJ), although only 1 to 5 bp of precise homology is sufficient for end joining in S. cerevisiae (29,33,34). This might explain why these nonhomologous events occur 1 to 2 orders of magnitude less frequently than SSA.…”
mentioning
confidence: 99%
“…Endjoining reactions also differ from classical homologous recombination in that they are typically nonconservative, such that the joining process results in a loss or gain in nucleotide base number (41,46). End joining in a wide array of organisms has been studied, from higher eucaryotes (14, 30,41,47) or simple eucaryotes (13,29,33,34,53,54,60) to bacteria (7,27). Even though the systems and the methods used to study end joining vary, the joint molecules formed are strikingly similar.…”
mentioning
confidence: 99%
“…Numerous studies of S. cerevisiae have been done to address the effect of sequence heterogeneity on mitotic recombination rates (5,15,23,31,32,42,51,56), and several of these have investigated the possible involvement of the yeast mismatch repair machinery in regulating homeologous interactions (4,5,42,56). These studies used substrates with less than 85% homology, and while all found at least a 15-fold effect of sequence divergence on recombination rates in wild-type strains, the magnitude of the effect was quite variable.…”
mentioning
confidence: 99%